Direct NMR resonance assignments of the active site histidine residue in Escherichia coli thioesterase I/protease I/lysophospholipase L1 - Wu, Wen-Jin (Magnetic resonance in chemistry : MRC, 2006)
Copyright 2006 John Wiley & Sons, Ltd.